Solid polymorphs of FLNA-binding compounds and their hydrochloride salts

By preparing various crystalline and amorphous forms of 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one, the stability problem is solved, and the stable crystalline form of the compound is achieved, which is suitable for the preparation of pharmaceutical compositions.

CN114072406BActive Publication Date: 2025-03-18CASSAVA SCI INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080030057.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-02-21
Filing Date
2020-02-21
Publication Date
2025-03-18
Estimated Expiration
2040-02-21

AI Technical Summary

Technical Problem

The prior art is difficult to provide a stable crystalline form of 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one, affecting its treatment and processing in pharmaceutical compositions.

Method used

By preparing various crystalline and amorphous forms of the compound, including its mono- and dihydrochloride polymorphs and its solvates, the characteristic peaks are identified by X-ray powder diffraction patterns to determine their stable form.

Benefits of technology

A variety of stable crystalline forms are provided, especially suitable for the preparation of solid oral compositions, which improves the chemical stability and shelf life of the compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114072406B_ABST
    Figure CN114072406B_ABST
Patent Text Reader

Abstract

The present invention discloses crystalline polymorphs and solvates of 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decane-2-one free base, and the preparation and properties of mono- and dihydrochlorides and solvates thereof, and amorphous polymorphs of dihydrochloride. Also disclosed are pharmaceutical compositions containing one or more polymorphs and methods of using the compositions.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Application Serial No. 62 / 808,609, filed on February 21, 2019, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to solid polymorphs of 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one, a compound that binds tightly to the protein filamin-A (FLNA), or polymorphs of the mono- or dihydrochloride salt of the compound. Background Art

[0004] 1-Benzyl-8-methyl-1,4,8-triazaspiro-[4.5]decan-2-one, the structural formula of which is shown below,

[0005]

[0006] Also known in the art as compounds C0105 and C0105M, and specifically binds to the protein filamin-A (FLNA). According to Wang et al. PlosOne 3(2):e1554 (2008) discussed the procedure, the effect of compound C0105 on tritiated naloxone {[ 3 Competition (shift) curves for inhibition of NLX} binding showed an EC50 value of approximately 10 for the higher affinity binding site of the two such sites identified. -12 Up to 10 -13 M. Using an N-biotinylated pentapeptide present in the FLNA sequence (Bn-VAKGL; SEQ ID NO: 1) instead of the membrane preparation provided EC50 values ​​of similar size to those obtained with the membrane preparation and indicated the presence of a single affinity site in the pentamer.

[0007] Compound C0105 is disclosed, synthesized and claimed in U.S. Pat. No. 8,653,068. The preparation of a pharmaceutically acceptable salt of Compound C0105 is also disclosed, although no such salt is specifically prepared, the compound is isolated and used only as an orange / yellow gum that can be readily identified by HPLC and depending on the formulation used. 1 The purity was found to be about 86 to about 97% by H-NMR.

[0008] Contacting suitable cells with compound C0105 can, among other things, reduce inflammatory responses (U.S. Pat. No. 8,653,068), inhibit phosphorylation of tau protein and formation of tau-containing plaques (U.S. Pat. No. 10,017,736), and inhibit the growth of certain cancer cells that contain increased amounts of one or more of phosphorylated mTOR, Akt1, ERK2, and serine 2152-phosphorylated filamin A relative to non-cancerous cells, as disclosed in U.S. Pat. No. 9,433,604, and for the treatment of Alzheimer's disease, as disclosed in U.S. Pat. Nos. 10,222,368 and Wang et al. J Prev Alz Dis, 2020, published online February 7, 2020. Compound C0105 can be used for diagnosis of Alzheimer's disease (AD) in living patients, for determining the effectiveness of AD therapies, and for trials for treating AD, as taught in U.S. Pat. Nos. 9,354,223, 9,500,640, and 10,222,368, respectively.

[0009] In the formulation of pharmaceutical compositions of active pharmaceutical ingredients (APIs, compounds or drugs), it is important that the drug substance is in a form that allows it to be conveniently handled and processed. This is important not only from the perspective of obtaining a commercially viable manufacturing process, but also from the perspective of the subsequent preparation of pharmaceutical formulations containing the active compound. Gum is not in such a convenient form to handle and process.

[0010] Chemical stability, solid state stability and shelf life of the active ingredient are also important factors. The drug substance and compositions containing it should be able to be effectively stored for a considerable period of time without significant changes in the physicochemical properties of the active ingredient (e.g., its chemical composition, density, hygroscopicity and solubility).

[0011] In addition, it is also important to be able to provide the drug in the purest form possible. Compared with crystalline materials, amorphous materials may present significant problems in this regard. For example, such materials are generally more difficult to handle and formulate than crystalline materials, provide unreliable solubility, and are often found to be unstable and chemically impure. The skilled person understands that if the active pharmaceutical ingredient (API) can be easily obtained in a stable crystalline form, the above problems can be greatly alleviated if not resolved.

[0012] Therefore, in the preparation of commercially viable and pharmaceutically acceptable pharmaceutical compositions, it is desirable to provide the API in a substantially crystalline and stable form whenever possible. However, it should be noted that this goal is not always achievable. In practice, it is generally not possible to predict from the molecular structure alone what the crystallization and post-crystallization behavior of a compound will be, and these behaviors can usually only be determined empirically. Summary of the invention

[0013] The present invention relates to solid polymorphs of 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one, solvates thereof, and polymorphs of the mono- and dihydrochloride salts of the compound and solvates thereof.

[0014] In one aspect, solid forms and pharmaceutically acceptable solvates of compounds of formula III

[0015]

[0016] Its X-ray powder diffraction pattern shows characteristic peaks defined below

[0017] a) A crystalline monohydrate Form 1 characterized by:

[0018] An X-ray powder diffraction pattern having at least one peak selected from 8.0, 13.0, 13.8, 19.1 and 20.2 2θ ± 0.2° 2θ; or

[0019] Basically similar to Figure 1 X-ray powder diffraction pattern of

[0020] b) a crystalline monohydrate form 2 characterized by:

[0021] an X-ray powder diffraction pattern having at least one peak selected from 9.9, 11.9, 13.2, 14.2, 15.8, 20.0 and 20.4 2θ ± 0.2° 2θ; or

[0022] Basically similar to Figure 2 X-ray powder diffraction pattern of

[0023] c) Crystalline dimethylacetamide solvate Form 3, characterized in that:

[0024] An X-ray powder diffraction pattern having a peak at 5.5 2θ ± 0.2° 2θ; or

[0025] Basically similar to Figure 3 X-ray powder diffraction pattern of

[0026] (d) Amorphous Form 4, characterized in that:

[0027] Basically similar to Figure 4 An X-ray powder diffraction pattern of

[0028] (e) Crystalline monohydrate Form 5, characterized in that:

[0029] An X-ray powder diffraction pattern having a peak at 22.4 2θ ± 0.2° 2θ; or

[0030] Basically similar to Figure 5 X-ray powder diffraction pattern of .

[0031] The crystalline form of the compound of formula II is selected from

[0032]

[0033] (a) Form 1, characterized in that:

[0034] An X-ray powder diffraction pattern having at least one peak selected from 12.4, 20.5, 21.7 and 25.5 2θ ± 0.2° 2θ; or

[0035] Basically similar to Figure 6 X-ray powder diffraction pattern of

[0036] (b) Form 2, characterized in that:

[0037] An X-ray powder diffraction pattern having at least one peak selected from 10.5, 13.8 and 22.7 2θ±0.2° 2θ; or

[0038] Basically similar to Figure 7 An X-ray powder diffraction pattern of

[0039] (c) Form 3, characterized in that:

[0040] An X-ray powder diffraction pattern having at least one peak selected from 13.6, 15.8, 20.8, 22.0 and 27.2 2θ ± 0.2° 2θ; or

[0041] Basically similar to Figure 8 An X-ray powder diffraction pattern of

[0042] (d) Form 4, characterized in that:

[0043] an X-ray powder diffraction pattern having at least one peak selected from 11.2, 18.0 and 20.0 2θ ± 0.2° 2θ; or

[0044] Basically similar to Fig. 9 X-ray powder diffraction pattern of .

[0045] A crystalline form of a compound of formula I selected from

[0046]

[0047] a) Form 1, characterized in that:

[0048] an X-ray powder diffraction pattern having at least one peak selected from 24.1, 26.3 and 27.3 2θ ± 0.2° 2θ; or

[0049] Basically similar to Fig.10X-ray powder diffraction pattern of

[0050] b) Form 2, characterized in that:

[0051] An X-ray powder diffraction pattern having at least one peak selected from 13.1 and 16.8 2θ±0.2° 2θ; or

[0052] Basically similar to Fig.11 An X-ray powder diffraction pattern of

[0053] c) Form 3, characterized in that:

[0054] An X-ray powder diffraction pattern having at least one peak selected from 10.1, 14.1 and 19.3 2θ±0.2° 2θ; or

[0055] Basically similar to Fig.12 X-ray powder diffraction pattern of .

[0056] Another aspect of the present invention relates to a pharmaceutical composition comprising a crystalline or amorphous form of one or more compounds of Formula I, II or III as described above, which can be dissolved or dispersed in a physiologically tolerable carrier or diluent, which is effective in reducing or inhibiting tau protein phosphorylation, inhibiting the interaction of FLNA with α7nAChR and TLR4, inhibiting Aβ 42 The amount of one or more of interacting with α7 nAChR, inhibiting cancer cell growth as described above, reducing one or both of pain and inflammation, or treating and / or measuring Alzheimer's disease in a living patient.

[0057] In living patients, it reduces or inhibits tau phosphorylation, inhibits the interaction of FLNA with α7nAChR and TLR4, and inhibits Aβ 42 The method of interacting with α7 nAChR, inhibiting cancer cell growth, reducing one or both of pain and inflammation, or treating and / or measuring Alzheimer's disease comprises administering the above-mentioned pharmaceutical composition to the host mammal. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] In the accompanying drawings which form a part of this disclosure,

[0059] Figure 1 is an X-ray powder diffraction pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 1;

[0060] Figure 2is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 2;

[0061] Figure 3 is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride dimethylacetamide solvate, Form 3;

[0062] Figure 4 is an X-ray powder diffraction (XRPD) pattern of amorphous 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride, Form 4;

[0063] Figure 5 is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 5;

[0064] Figure 6 is an X-ray powder diffraction pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 1;

[0065] Figure 7 is an X-ray powder diffraction pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 2;

[0066] Figure 8 is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 3;

[0067] Fig. 9 is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 4;

[0068] Fig.10 is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one free base, Form 1;

[0069] Fig.11 is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one free base, Form 2; and

[0070] Fig.12 This is an X-ray powder diffraction (XRPD) pattern of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one free base, Form 3.

[0071] The present invention has several benefits and advantages.

[0072] One benefit is that it provides a variety of APIs in crystalline and stable forms.

[0073] An advantage of the present invention is that one of those crystalline and stable forms of 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride is particularly suitable for the preparation of solid oral compositions.

[0074] Another advantage of the present invention is that it provides a particularly stable hydrated dihydrochloride salt.

[0075] Another advantage of the present invention is that it provides an amorphous polymorph of the dihydrochloride salt.

[0076] Other benefits and advantages will be apparent to those skilled in the art from the following description and claims. DETAILED DESCRIPTION

[0077] The present invention relates to a polymorphic form of the compound 1-benzyl-8-methyl-1,4,8-triazaspiro[4.5]-decan-2-one, whose structural formula I is shown below, and

[0078]

[0079] Polymorphs of its mono- and dihydrochloride salts, and pharmaceutically acceptable solvates thereof (pharmaceutically acceptable solvated forms). The compound of formula I is also known in the art as compound C0105 (also known as C0105M). Those polymorphs of the free base, mono- or dihydrochloride salts or solvates thereof are identified by peaks in their X-ray powder diffraction (XRPD) spectra.

[0080] Polymorphs of a solid form of a molecule are usually defined by one or more characteristic peaks expressed as scattering angle position values ​​of 2θ (°2θ), ±0.2°. Other characteristic data for each polymorphic form include d-spacing, which is a measure of the distance between the molecular planes of the crystalline form related to a particular °2θ peak, and the relative intensity of each identified peak as a percentage of the maximum intensity peak.

[0081] The characteristic scattering pattern (diffraction pattern) for identifying a specific crystalline polymorph may contain only a single peak that is unique to the specific polymorph. It is considered that better practice is to use 3 to 5 peaks, more preferably, to use more than 5 peaks to identify a specific polymorph. Therefore, in the case where only 1 or 2 marker peaks are unique to a specific polymorph, and one or more other peaks are shared (overlapped) with peaks produced by another polymorph, the unique peak data using the data of 1 to 5 peaks with overlap can provide a determined diffraction pattern of a specific polymorph.

[0082] It is preferred that scatter peaks with a relative intensity of at least 5% of the intensity of the most intense peak be reported as members of a characteristic scatter pattern. However, in cases where few and / or lower relative intensity peaks are those observed and reported for a characteristic scatter pattern.

[0083] The characteristic 2θ positions, d spacings and intensity percentages of twelve expected polymorphs of compound C0105 are provided in the table below, as free base and as its two-(bis-) and monohydrochloride salts and solvates thereof. Each °2θ measurement in the table below is ± 0.2°, which is not shown in the table for clarity in the table. Data are typically reported as scattering angles of up to about 20 to about 30 °2θ.

[0084] At least one XRPD marker peak can be used to identify a specific crystalline form of a compound known to be a free base, a monohydrochloride or a dihydrochloride salt or a solvate thereof. Preferably, at least 3 XRPD marker peaks are used, and more preferably, 5 or more additional XRPD marker peaks are used when an XRPD marker peak is present in the diffraction pattern. As can be seen from the figures herein, the number of distinguishable peaks may be different in various crystalline forms of the free base or hydrochloride salt.

[0085] One or more "marker peaks" are used to identify XRPD peaks that are unique to a particular polymorph and can be used to identify that polymorph. The phrase "total X-ray powder diffraction pattern" is used to count and identify peaks in the diffraction pattern, whether or not they are marker peaks. The phrase "peaks that overlap slightly with other forms" are those peaks that have one or more marker peaks that can be used to identify a particular polymorph.

[0086] The phrase "pharmaceutically acceptable solvate" is used to refer to solvent molecules that form part of the crystallization matrix of the desired polymorph. Solvates are named with the name of the solvent followed by the word "solvate", except when water is the solvate, in which case the word "hydrate" is used. "Pharmaceutically acceptable solvates" include solvents that may be present in a drug product in accordance with local or national drug laws and regulations, such as those of the U.S. FDA. Thus, exemplary solvates include hydrates, methanol solvates, ethanol solvates, isopropanol solvates, dimethylacetamide solvates, and the like.

[0087] The pharmaceutical composition can be prepared by dissolving or dispersing an effective amount of the desired polymorph or a solvate thereof in a physiologically tolerable carrier or diluent. A "physiologically tolerable carrier or diluent" is a diluent or carrier that may be present in a pharmaceutical product according to local or national pharmaceutical laws and regulations, such as those of the U.S. FDA.

[0088] Polymorphs are indicated by the word "form" followed by an Arabic numeral. The numerals are used only for the convenience of distinguishing one polymorph from another and for no other purpose.

[0089] Characterization of crystal forms

[0090] Figure 1 The X-ray powder diffraction pattern (XRPD) of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 1 was obtained using a Philips Pananalytical X'Pert powder Materials Research diffractometer (MRD) instrument over a 3°-35° 2θ scan range with 0.013° 2θ increments. The X-rays were generated by a copper anode operating at 40 kV and 40 mA. The wavelength of the X-rays was 1.5406 Ȧ. Table 1 lists the XRPD patterns of crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 1. Figure 1 Positions, °2θ±0.2°2θ, d-spacings and relative intensities of peaks identified in the experimental XRPD pattern of.

[0091] The entire list of peaks or a unique subset thereof is sufficient to characterize the crystalline form, and Figure 1 Substantially similar XRPD patterns (i.e., identifiable by one of ordinary skill in the art using characterization methods such as this method within experimental variation). Table 2 lists Figure 1 The peaks identified in the experimental XRPD pattern of , which do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs, and which represent the preferred peaks used to identify the crystalline form.

[0092] Table 1

[0093] Position [°2θ] d-spacing Å Strength (in %) 8.0 11.09 5.2 9.2 9.58 100.0 13.0 6.81 10.8 13.8 6.41 8.1 15.4 5.77 57.3 16.1 5.52 5.4 19.1 4.65 39.8 19.7 4.51 35.1 20.2 4.39 19.7 21.7 4.10 5.9 22.8 3.90 5.2 23.2 3.83 7.3 24.2 3.68 18.5

[0094] Peaks present below 2θ = 25 and with % intensity greater than 5% were selected.

[0095] Table 2

[0096] Position [°2θ] d-spacing Å Strength (in %) 8.0 11.09 5.2 13.0 6.81 10.8 13.8 6.41 8.1 19.1 4.65 39.8 20.2 4.39 19.7

[0097] Peaks present below 2θ = 25° and with % intensity greater than 5% were selected.

[0098] C0105 Bis-HCl Salt Monohydrate: Form 2

[0099] Chemical formula: C15H23Cl2N3O.H2O

[0100] Figure 2 Yes Figure 1 The X-ray powder diffraction (XRPD) pattern of the obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 2.

[0101] Table 3 lists the Figure 2 The positions, °2θ±0.2°2θ, d-spacings, and relative intensities of the peaks identified in the experimental XRPD pattern of the present invention. The entire list of peaks or a unique subset thereof may be sufficient to characterize the crystalline form, and the crystalline form may be characterized by the presence of a peak in the form of a crystalline form. Figure 2 Substantially similar XRPD patterns (ie, identifiable by one of ordinary skill using a characterization method such as this characterization method within experimental variation).

[0102] Table 4 lists the peaks that do not overlap with peaks in the XRPD diffraction patterns of other polymorphs, which represent the preferred peaks used to identify the crystalline form.

[0103] Table 3

[0104]

[0105] Peaks present below 2θ = 30 and with % intensity greater than 5% were selected.

[0106] Table 4

[0107] Position [°2θ] d-spacing Å Strength (in %) 9.9 8.89 91.3 11.9 7.42 4.7* 13.2 6.71 100.00 14.2 6.24 7.5 15.8 5.61 18.4 20.0 4.45 23.0 20.4 4.35 12.0

[0108] The peaks presented were chosen to be below 2θ = 25 and with % intensity greater than 5%, with the exception of the *peaks which were uniquely positioned.

[0109] C0105 Bis-HCl Salt DMA Solvate: Form 3

[0110] Chemical formula: C15H23Cl2N3O.C4H9NO

[0111] Figure 3 is an X-ray powder diffraction (XRPD) pattern, which is Figure 1 The X-ray powder diffraction pattern of the obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one dihydrochloride dimethylacetamide solvate, Form 3, is different in that the peaks given are all detectable peaks.

[0112] Table 5 lists the Figure 3The positions, °2θ±0.2°2θ, d-spacings, and relative intensities of the peaks identified in the experimental XRPD pattern of the present invention. The entire list of peaks or a subset thereof may be sufficient to characterize the crystalline form, and the crystalline form may be characterized by the presence of a peak. Figure 3 Substantially similar XRPD patterns (ie, identifiable by one of ordinary skill using a characterization method such as this characterization method within experimental variation).

[0113] Table 6 lists the Figure 3 The peaks identified in the experimental XRPD pattern of , which do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs, and which represent the preferred peaks used to identify the crystalline form.

[0114] Table 5

[0115] Position [°2θ] d-spacing Å Strength (in %) 5.5 16.07 100.0 9.1 9.67 3.5 16.0 5.54 44.1 17.4 5.11 18.6 19.6 4.53 13.5

[0116] The peaks presented are all peaks that can be detected as samples presenting a minority of peaks.

[0117] Table 6

[0118] Position [°2θ] d-spacing Å Strength (in %) 5.5 16.07 100.0

[0119] C0105 Bis-HCl Salt: Form 4 - Amorphous

[0120] Chemical formula: C15H23Cl2N3O

[0121] Figure 4 is an X-ray powder diffraction (XRPD) pattern of amorphous 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride, Form 4, obtained using a Siemens D5000 diffractometer over a scan range of 3°-30.0° 2θ with 0.02° 2θ increments. X-rays were generated by a copper anode operating at 40 kV and 40 mA. No peaks were observed, indicating an amorphous solid state form.

[0122] C0105 Bis-HCl Salt Monohydrate: Form 5

[0123] Chemical formula: C15H23Cl2N3O.H2O

[0124] Figure 5 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one dihydrochloride monohydrate, X-ray powder diffraction (XRPD) pattern of Form 5, except that the peak presented is selected so as to have at least 5% of the strongest peak intensity and be below 2θ = 30°.

[0125] Table 7 lists the Figure 5The positions, °2θ±0.2°2θ, d-spacings, and relative intensities of the peaks identified in the experimental XRPD pattern of the present invention. The entire list of peaks or a unique subset thereof may be sufficient to characterize the crystalline form, and the crystalline form may be characterized by the presence of a peak in the form of a crystalline form. Figure 5 Substantially similar XRPD patterns (ie, identifiable by one of ordinary skill using a characterization method such as this characterization method within experimental variation).

[0126] Table 8 lists the Figure 5 The peaks identified in the experimental XRPD pattern of the polymorph do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs, and they represent the preferred peaks used to identify the crystalline form. Table 9 lists the peaks identified in the experimental XRPD pattern of the polymorph. Figure 5 The characteristic peaks identified in the experimental XRPD pattern of , which may slightly overlap with the peaks in the XRPD diffraction patterns of other polymorphs.

[0127] Table 7

[0128]

[0129] Peaks were selected to be present below 2θ = 30 and with % intensity greater than 5%.

[0130] Table 8

[0131] Position [°2θ] d-spacing Å Strength (in %) 22.4 3.96 27.6

[0132] Peaks were selected to be present below 2θ = 30 and with % intensity greater than 5%.

[0133] Table 9

[0134]

[0135] Peaks were selected to be present below 2θ = 30 and with % intensity greater than 5%.

[0136] C0105 mono-HCl salt: Form 1

[0137] Chemical formula: C15H22ClN3O

[0138] Figure 6 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one monohydrochloride, X-ray powder diffraction (XRPD) pattern of Form 1, except that the peaks presented are selected so as to have at least 5% of the strongest peak intensity and be below 2θ = 30°.

[0139] Table 10 lists the Figure 6 The positions, °2θ±0.2°2θ, d-spacings and relative intensities of the peaks identified in the experimental XRPD pattern. The entire list of peaks or a subset thereof may be sufficient to characterize the crystalline form, and by comparing Figure 6Substantially similar XRPD patterns (i.e., identifiable by one of ordinary skill using characterization methods such as this characterization method over experimental variations).

[0140] Table 11 lists the Figure 6 The peaks identified in the experimental XRPD pattern of the polymorph do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs, and they represent the preferred peaks used to identify the crystalline form. Table 12 lists the peaks identified in the experimental XRPD pattern of the polymorph. Figure 6 The characteristic peaks identified in the experimental XRPD pattern of , which may slightly overlap with the peaks in the XRPD diffraction patterns of other polymorphs.

[0141] Table 10

[0142] Position [°2θ] d-spacing Å Strength (in %) 7.0 12.64 43.8 11.5 7.68 27.0 12.4 7.17 25.7 14.1 6.29 89.5 14.6 6.08 23.4 16.3 5.45 53.3 16.5 5.37 100.0 17.6 5.04 5.3 18.7 4.76 31.5 18.8 4.71 59.4 19.6 4.53 17.7 19.9 4.47 62.2 20.2 4.39 9.0 20.5 4.33 29.8 21.5 4.14 54.9 21.7 4.10 77.6 22.7 3.91 48.8 23.2 3.84 65.4 24.8 3.59 7.6 25.5 3.49 19.7 26.4 3.38 33.9 26.7 3.34 16.0 28.4 3.14 37.9 28.7 3.11 59.9 28.9 3.09 20.0 29.4 3.04 9.8 29.7 3.01 14.8

[0143] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0144] Table 11

[0145] Position [°2θ] d-spacing Å Strength (in %) 12.4 7.17 25.7 20.5 4.33 29.8 21.7 4.10 77.6 25.5 3.49 19.7

[0146] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0147] Table 12

[0148]

[0149] Peaks were selected to be present below 2θ = 30 and with % intensity greater than 5%.

[0150] C0105 mono-HCl salt: Form 2

[0151] Chemical formula: C15H22ClN3O

[0152] Figure 7 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one monohydrochloride, X-ray powder diffraction (XRPD) pattern of Form 2, except that the peaks presented are selected so as to have at least 5% of the strongest peak intensity and be below 2θ = 30°.

[0153] Table 13 lists the Figure 7 The positions, °2θ±0.2°2θ, d-spacings and relative intensities of the peaks identified in the experimental XRPD pattern. The entire list of peaks or a subset thereof may be sufficient to characterize the crystalline form, and by comparing Figure 7 Substantially similar XRPD patterns (i.e., identifiable by one of ordinary skill using characterization methods such as this method within experimental variation).

[0154] Table 14 lists the Figure 7 The peaks identified in the experimental XRPD pattern of , which do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs, and represent the preferred peaks used to identify the crystalline form.

[0155] Table 13

[0156] Position [°2θ] d-spacing Å Strength (in %) 7.0 12.67 5.9 10.5 8.43 100.0 13.8 6.42 7.5 14.1 6.30 16.4 16.2 5.47 8.7 16.5 5.38 6.7 18.7 4.75 24.0 21.5 4.14 11.2 22.7 3.92 21.6 23.2 3.83 11.0 28.4 3.14 5.4

[0157] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0158] Table 14

[0159] Position [°2θ] d-spacing Å [ Å] Strength (in %) 10.5 8.43 100.0 13.8 6.42 7.5 22.7 3.92 21.5

[0160] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0161] C0105 mono-HCl salt: Form 3

[0162] Chemical formula: C15H22ClN3O

[0163] Figure 8 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one monohydrochloride, Form 3 has an X-ray powder diffraction (XRPD) pattern, except that the peaks presented are selected so as to have at least 5% of the strongest peak intensity and be below 2θ = 30°. Table 15 lists the Figure 8 The positions, °2θ±0.2°2θ, d-spacings and relative intensities of the peaks identified in the experimental XRPD pattern.

[0164] The entire list of peaks or a subset thereof is sufficient to characterize the polymorph, and Figure 8 Substantially similar XRPD patterns (ie, identifiable by one of ordinary skill in the art using characterization methods such as this method within experimental variations).

[0165] Table 16 lists the Figure 8 The peaks identified in the experimental XRPD pattern of the polymorph do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs and represent the preferred peaks used to identify the crystalline form. Table 17 lists the peaks identified in the experimental XRPD pattern of the polymorphs. Figure 8 The characteristic peaks identified in the experimental XRPD pattern of , which may slightly overlap with the peaks in the XRPD diffraction patterns of other polymorphs.

[0166] Table 15

[0167] Position [°2θ] d-spacing [Å] Strength (in %) 10.3 8.57 30.2 13.6 6.49 85.1 14.6 6.06 23.4 15.8 5.62 17.9 16.3 5.44 8.1 17.2 5.15 100.0 18.9 4.71 76.2 20.8 4.27 53.4 21.3 4.17 25.2 22.0 4.03 39.9 23.0 3.86 55.7 24.0 3.71 71.5 25.2 3.54 11.7 26.1 3.41 31.0 27.2 3.28 27.1 27.7 3.22 14.6 28.2 3.16 83.8

[0168] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0169] Table 16

[0170] Position [°2θ] d-spacing [Å] Strength (in %) 13.6 6.49 85.1 15.8 5.62 17.9 20.8 4.27 53.4 22.0 4.03 39.9 27.2 3.28 27.1

[0171] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0172] Table 17

[0173] Position [°2θ] d-spacing [Å] Strength (in %) 10.3 8.57 30.2 23.1 3.86 55.7 24.0 3.71 71.5

[0174] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0175] C0105 mono-HCl salt: Form 4

[0176] Chemical formula: C15H22ClN3O

[0177] Fig. 9 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one monohydrochloride, Form 4 X-ray powder diffraction (XRPD) pattern, except that the peaks presented are selected so as to have at least 5% of the strongest peak intensity and below 2θ = 30°. Table 18 lists the Fig. 9 The positions, °2θ±0.2°2θ, d-spacings and relative intensities of the peaks identified in the experimental XRPD pattern of the present invention. The entire peak list or a subset thereof may be sufficient to characterize the crystalline form, and the peaks identified in the experimental XRPD pattern of the present invention may be sufficient to characterize the crystalline form. Fig. 9 Substantially similar XRPD patterns (i.e., identifiable by one of ordinary skill using characterization methods such as this method over a range of experimental variation).

[0178] Table 19 lists the Fig. 9 The peaks identified in the experimental XRPD pattern of the polymorph do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs and represent the preferred peaks for identifying the crystalline form. Table 20 lists the peaks identified in the experimental XRPD pattern of the polymorphs. Fig. 9 The characteristic peaks identified in the experimental XRPD pattern of , which may slightly overlap with the peaks in the XRPD diffraction patterns of other polymorphs.

[0179] Table 18

[0180]

[0181] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0182] Table 19

[0183]

[0184] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0185] Table 20

[0186]

[0187] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0188] C0105 Free Base: Form 1

[0189] Chemical formula: C15H21N3O

[0190] Fig.10 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one free base, Form 1, has an X-ray powder diffraction (XRPD) pattern, except that the peaks presented are selected so as to have at least 5% of the strongest peak intensity and be below 2θ = 30°.

[0191] Table 21 lists the Fig.10 The positions, °2θ±0.2°2θ, d-spacings, and relative intensities of the peaks identified in the experimental XRPD pattern of the present invention. The entire list of peaks or a subset thereof may be sufficient to characterize the crystalline form, and the crystalline form may be characterized by the presence of a peak. Fig.10 Substantially similar XRPD patterns (ie, identifiable by one of ordinary skill using a characterization method such as this characterization method within experimental variation).

[0192] Table 22 lists the Fig.10 The peaks identified in the experimental XRPD pattern of the polymorph do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs and represent the preferred peaks used to identify the crystalline form. Table 23 lists the peaks identified in the experimental XRPD pattern of the polymorphs. Fig.10 The characteristic peaks identified in the experimental XRPD pattern of , which may slightly overlap with the peaks in the XRPD diffraction patterns of other polymorphs.

[0193] Table 21

[0194] Position [°2θ] d-spacing Å Strength (in %) 8.7 10.21 25.4 12.4 7.14 38.8 12.7 6.97 11.9 15.6 5.68 12.5 16.4 5.42 100.0 17.3 5.13 10.6 17.9 4.96 22.7 18.6 4.77 5.6 19.1 4.65 30.9 19.9 4.46 11.3 20.3 4.37 29.2 24.1 3.69 15.0 24.8 3.59 39.4 25.0 3.56 14.1 25.2 3.53 5.6 26.3 3.39 6.4 27.3 3.27 6.5 27.6 3.24 10.8 28.3 3.15 8.8

[0195] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0196] Table 22

[0197]

[0198] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0199] Table 23

[0200]

[0201] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0202] C0105 Free Base: Form 2

[0203] Chemical formula: C15H21N3O

[0204] Fig.11 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one free base, Form 2, has an X-ray powder diffraction (XRPD) pattern, except that the peaks presented are selected so as to have at least 5% of the strongest peak intensity and be below 2θ = 30°. Table 24 lists the Fig.11 Positions, °2θ±0.2°2θ, d-spacings and relative intensities of the peaks identified in the experimental XRPD pattern.

[0205] The entire list of peaks or a subset thereof is sufficient to characterize the polymorph, and Fig.11 Substantially similar XRPD patterns (i.e., identifiable by one of ordinary skill in the art using characterization methods such as this method within experimental variation). Table 25 lists Fig.11 The peaks identified in the experimental XRPD pattern of , which do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs, and represent the preferred peaks used to identify the crystalline form.

[0206] Table 26 lists the Fig.11 The characteristic peaks identified in the experimental XRPD pattern of , which may slightly overlap with the peaks in the XRPD diffraction patterns of other polymorphs.

[0207] Table 24

[0208] Position [°2θ] d-spacing [Å] Strength (in %) 8.3 10.66 9.7 10.9 8.09 100.0 13.1 6.74 13.8 15.5 5.71 12.4 16.2 5.48 60.8 16.8 5.27 20.8 21.7 4.10 13.2 22.1 4.02 47.9 25.3 3.52 68.4

[0209] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0210] Table 25

[0211]

[0212] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0213] Table 26

[0214]

[0215] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0216] C0105 Free Base: Form 3

[0217] Chemical formula: C15H21N3O

[0218] Fig.12 Yes Figure 4 The obtained crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one free base, Form 3, has an X-ray powder diffraction (XRPD) pattern, except that the peaks presented are selected so as to have at least 5% of the strongest peak intensity and below 2θ = 30°. Table 27 lists the Fig.12 Positions, °2θ±0.2°2θ, d-spacings and relative intensities of the peaks identified in the experimental XRPD pattern of.

[0219] The entire list of peaks or a subset thereof is sufficient to characterize the polymorph, and Fig.12 Substantially similar XRPD patterns (ie, identifiable by one of ordinary skill in the art using characterization methods such as this method within experimental variations).

[0220] Table 28 lists the Fig.12 The peaks identified in the experimental XRPD pattern of the polymorph do not overlap with the peaks in the XRPD diffraction patterns of other polymorphs and represent the preferred peaks used to identify the crystalline form. Table 29 lists the peaks identified in the experimental XRPD pattern of the polymorphs. Fig.12 The characteristic peaks identified in the experimental XRPD pattern of , which may slightly overlap with the peaks in the XRPD diffraction patterns of other polymorphs.

[0221] Table 27

[0222] Position [°2θ] d-spacing Å Strength (in %) 10.1 8.78 100.0 11.0 8.03 5.4 12.2 7.27 16.7 14.3 6.19 61.7 16.0 5.53 13.6 16.2 5.47 40.4 17.8 4.99 63.7 18.5 4.79 66.5 18.7 4.75 55.5 19.3 4.59 24.5 19.9 4.46 8.9 20.2 4.40 27.6 21.4 4.15 14.8 21.6 4.12 14.6 22.3 3.98 20.4 22.8 3.90 14.4 27.8 3.21 5.8 28.1 3.18 9.2 28.2 3.16 10.7 29.8 2.99 5.5

[0223] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0224] Table 28

[0225]

[0226] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0227] Table 29

[0228]

[0229] Peaks were selected to be present below 2θ = 30° and with % intensity greater than 5%.

[0230] Pharmaceutical composition

[0231] The expected compound polymorph or solvate form can be used alone in salt or free base form. Regardless of whether it is in salt form or solvate form, an effective amount of the expected solid polymorph is usually dissolved or dispersed in a physiologically tolerable carrier or diluent, which forms a pharmaceutical composition, and the polymorph is an API, usually the only API. Such a pharmaceutical composition is administered to the CNS and / or other cells in vitro or in vivo so that the API binds to FLNA and exemplarily inhibits tau protein phosphorylation, inhibits the interaction of FLNA with α7nAChR and TLR4, and inhibits Aβ 42 Interaction with α7nAChR may reduce either or both pain and inflammation.

[0232] The expected polymorph can be used to prepare a drug (pharmaceutical composition) that can be used to inhibit tau protein phosphorylation in mammalian cells and mammalian cell preparations. The expected solid polymorph compound can also be used to prepare a drug that is used to inhibit the binding of FLNA to α7nAChR and TLR4 and Aβ 42 Interaction with α7 nAChR, or reducing one or both of pain and inflammation in mammalian cells and mammalian cell preparations.

[0233] The intended pharmaceutical composition contains an effective amount of the intended API polymorph (free base polymorph or mono- or dihydrochloride hydrate or dihydrochloride hydrate or other solvated form) dissolved or dispersed in a physiologically tolerable carrier or diluent as described above. Such compositions can be administered to mammalian cells or cell preparations in vitro, such as in cell culture or protein binding studies, or in vivo, such as in a living host mammal in need thereof.

[0234] The intended composition is typically administered multiple times to a living recipient over a period of days, weeks, or months. More typically, the contemplated composition is administered once, twice, or more times per day, with the administration repeated. It is contemplated that once administration of the intended polymorph is initiated, the polymorph will be administered long-term, for example, for the duration of the study or for the lifetime of the recipient.

[0235] The expected free base polymorph can bind FLNA at 100 femtomolar concentrations and effectively inhibit cytokine release from LPS-stimulated astrocytes in vitro. The expected polymorph mono- or dihydrochloride salts bind at about the same molar concentration as the free base and bind at a proportional weight percentage based on the free base. The expected polymorph is more typically used in picomolar to micromolar amounts.

[0236] Thus, in practicing the contemplated methods of the present invention, an effective amount of a contemplated polymorph present in a contemplated pharmaceutical composition is an amount that provides a concentration of about 100 femtomolar to about 10 micromolar to the bloodstream of a host animal or to an in vitro cell culture medium. Amounts of about picomolar to about micromolar are more commonly used. Amounts of about picomolar to about nanomolar are more commonly used. A skilled artisan can readily determine the appropriate dosage level for a contemplated compound to inhibit the desired amount of FLNA binding.

[0237] The intended pharmaceutical composition can be administered orally (perorally), parenterally, by inhalation spray in the form of a formulation containing conventional non-toxic pharmaceutically acceptable carriers, adjuvants and required excipients. The term parenteral as used herein includes subcutaneous injection, intravenous, intramuscular, intrasternal injection or infusion techniques. The formulation of the drug is described in, for example, Hoover, John E., Remington's Pharmaceutical Sciences , Mack Publishing Co., Easton, Pennsylvania, 1975 and Liberman, HA and Lachman, L., Eds., Pharmaceutical Dosage Forms , Marcel Decker, New York, NY, 1980.

[0238] For injectable preparations, for example, sterile injectable aqueous or oily solutions or suspensions can be prepared using suitable dispersants or wetting agents and suspending agents according to known techniques. Sterile injectable preparations can also be sterile injectable solutions or suspensions in nontoxic parenterally acceptable diluents or solvents, for example as solutions in 1,3-butanediol.

[0239] When a solid polymorph API is required to be in solution form, the compound is generally provided in solid form, preferably without liquid, or in the form of a suspension in a non-solvent liquid to which a solvent such as normal saline is added to dissolve the solid API polymorph. Among acceptable carriers and solvents, water, Ringer's solution and isotonic sodium chloride solution, phosphate buffered saline, can be used. Liquid pharmaceutical compositions include, for example, solutions suitable for parenteral administration. Sterile aqueous solutions of the API or sterile solutions of the API in solvents including water, ethanol or propylene glycol are examples of liquid compositions suitable for parenteral administration.

[0240] In addition, sterile fixed oils are generally used as solvents or suspension media. For this purpose, any mild fixed oil can be used, including synthetic monoglycerides or diglycerides. In addition, fatty acids such as oleic acid can be used to prepare injections. Dimethylacetamide, surfactants including ionic and nonionic detergents, polyethylene glycol can be used. Mixtures of solvents and wetting agents, such as those discussed above, are also useful.

[0241] Sterile solutions can be prepared under aseptic conditions by dissolving the desired polymorph in the desired solvent system and then passing the resulting solution through a membrane filter to sterilize it, or by dissolving the sterile compound in a pre-sterilized solvent.

[0242] Solid dosage forms for oral administration can include capsules, tablets, pills, powders and granules. In such solid dosage forms, the compound under consideration is usually combined with one or more excipients suitable for specifying the route of administration. If administered orally, the compound can be mixed with lactose, sucrose, starch powder, cellulose esters of C1-C6-alkanoic acid, cellulose C1-C6-alkyl esters, talcum, stearic acid, magnesium stearate, magnesium oxide, sodium salts and calcium salts of phosphoric acid and sulfuric acid, gelatin, gum arabic, sodium alginate, polyvinyl pyrrolidone and / or polyvinyl alcohol, and then tableted or loaded into capsules for convenient administration. This capsule or tablet can contain a controlled release formulation, such as the controlled release formulation provided in the dispersion of the active compound in hydroxypropyl methylcellulose. In the case of capsules, tablets and pills, the dosage form can also include a buffer, such as sodium citrate, magnesium carbonate or calcium carbonate or bicarbonate. Tablets, capsules and pills can be prepared with enteric coatings in addition.

[0243] The mammal in need of treatment and to which a pharmaceutical composition containing a desired solid polymorphic API or a solution containing a dissolved polymorphic API is administered can be a primate such as a human, an ape such as a chimpanzee or gorilla, a monkey such as a cynomolgus monkey or a rhesus monkey, a laboratory animal such as a rat, mouse or rabbit, a companion animal such as a dog, cat, horse, or a food animal such as a cow or steer, sheep, lamb, pig, goat, llama, etc. When in vitro mammalian cell contact is contemplated, CNS cell tissue cultures from exemplary mammals are typically used, as described below.

[0244] Preferably, the pharmaceutical composition is in unit dosage form. In this form, the composition is divided into unit doses containing appropriate amounts of active agents. The unit dosage form can be a packaged preparation that contains discrete amounts of the preparation, such as in a vial or ampoule.

[0245] Analytical procedures

[0246] Standard chemical analysis such as elemental analysis (CHN; ASTM D5291), high-resolution mass spectrometry (MS), 1 H-NMR, 13 C-NMR and 2D-NMR spectroscopy and infrared spectroscopy (IR) identify specific compounds, as performed by third-party suppliers. Physical property determinations are similarly performed using techniques such as X-ray particle diffraction (XRPD) for polymorph determination as discussed in detail herein, melting points by differential scanning calorimetry (DSC), and mass loss by thermogravimetric analysis (TGA). Water content is determined by Karl Fisher analysis. High pressure liquid chromatography (HPLC) is used to determine compound purity.

[0247] Polymorph preparation

[0248] Dihydrochloride Polymorph Form 1 Hydrate

[0249] Preparation 1

[0250] In some cases, the synthesis of compound C0105 (C0105M) was performed as discussed in U.S. Patent 8,653,068. An alternative synthesis was performed using the reaction schemes shown and discussed below.

[0251]

[0252] In the presence of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, triethylamine and ethyl cyano(oxime)acetate, Nt-Boc glycine is amidated with benzylamine in dichloromethane to form 2-amino-N-benzyl acetamide. The product is then converted to its hydrochloride by treatment with a 2-propanol (isopropanol) solution of HCl.

[0253] 2-Amino-N-benzylacetamide hydrochloride and isopropanol (8 volumes) were added to a flask. 1-Methylpiperidin-4-one (1.10 equiv.) was added to the suspension, followed by rinsing with methanol (2 volumes). The heterogeneous mixture was stirred at reflux for 20 hours. HPLC analysis after 20 hours showed a conversion rate of 94%. The solution was cooled to 45-55 (°C, 30% HCl (aq, 1.5 equiv.) was added dropwise to obtain a precipitate, the resulting slurry was cooled to ambient temperature, filtered after 3 hours, the separated solid was washed with MeOH (2×1 volumes), and the solid was air-dried to obtain 80% of the dihydrochloride hydrate of polymorph Form 1, whose X-ray powder diffraction (XRPD) spectrum is shown at Figure 1 Ethanol, ethyl acetate and tetrahydrofuran (THF) can also be used as solvents.

[0254] Convert mono-HCl to di-HCl hydrate salt

[0255] The HCl monosalt is mixed with 8 mL of 2-propanol, and the resulting suspension is stirred at about 50 ° C for about 1 hour, at which time a solution of 37% HCl (1.6 mL, 2 equivalents) in 1.6 mL of 2-propanol is added. The mixture is then initially cooled to ambient temperature, and then after equilibrium, an additional 5 mL of 2-propanol is added to the sample to about 2-3 ° C after cooling. The resulting white precipitate is filtered and washed with 2-propanol (2 × 7 mL aliquots). The separated solid is vacuum dried at ambient temperature for about 24 hours. Approximately 2g of monohydrate form 1 solid material (yield: 66%) is recovered. The polymorph can also be formed using ethanol, ethyl acetate or tetrahydrofuran instead of 2-propanol as a solvent.

[0256] Preparation 2

[0257]

[0258] Amide coupling of Boc-protected glycine with benzylamine

[0259] Nt-boc-glycine (0.808 kg) and ethyl acetate (EtOAc, 3.615 kg, 5.0 vols) were added to a nitrogen purged reactor and stirred until a clear solution was obtained. The solution was cooled to 0-5°C and benzylamine (0.534 kg, 1.10 eq) was added to the reactor while maintaining the cooled temperature. The dosing pellet was rinsed with EtOAc (0.50 vols) and the resulting EtOAc composition was added.

[0260] Triethylamine (Et3N, 2.2 eq., Et3N) was then added to the reactor with EtOAc (0.50 vol.) flush. 50% propanephosphonic anhydride (T3P) in EtOAc (3.493 kg, 1.20 eq.) and EtOAc flush (0.50 vol.) were added to the reactor while maintaining the temperature ≤ 25°C. The reaction mixture was stirred for 20 hours while maintaining the temperature at 20 ± 5°C. HPLC analysis showed 91% conversion of benzylamine.

[0261] Purified water (2.4 kg, 3.0 volumes) was added to form a 2-phase mixture, which was stirred for 9 minutes. The pH of the lower aqueous layer (target pH ≥ 7) was measured to be pH = 8. Phase separation occurred under static conditions, and the aqueous layer was removed and discarded.

[0262] Aqueous hydrochloric acid (30%; 0.032 kg, 0.03 volume) in purified water (2.4 kg, 3.0 volume) was added and the resulting 2-phase mixture was stirred for 8 minutes to form an intermediate salt product. The pH of the lower aqueous layer was measured (target pH ≤ 2) to be pH = 1. Phase separation occurred under static conditions and the aqueous layer was removed and discarded. HPLC analysis showed that the purity of the isolated intermediate N-Boc-2-amino-N-benzylacetamide was 97%.

[0263] While stirring, the reaction mixture was distilled under reduced pressure at 40°C ± 5°C to remove about 6 relative volumes of volatiles. Isopropanol (2.5 kg, 4 volumes) was added to the reactor. The reaction mixture was distilled at 40±5°C to remove about 4 relative volumes of volatiles. The reaction mixture was cooled to 20±5°C and maintained.

[0264] Cleavage of Boc protecting group

[0265] Isopropyl alcohol (IPA) was charged (3.2 kg, 5 volumes) to an empty reactor. Hydrogen chloride gas was fed under pressure into the reactor while stirring and cooling (15°-35°C) until approximately 5 equivalents were absorbed into the isopropyl alcohol.

[0266] Excess hydrogen chloride gas pressure in the reactor was vented. The intermediate reaction mixture prepared above was metered into the reactor under stirring and temperature control at 20°±5°C, the metering bulb was rinsed with isopropanol (0.329 kg, 0.50 volume), and the isopropanol composition was added to the reaction mixture. The reaction mixture temperature was controlled at 20±5°C and stirred for 20 hours. HPLC analysis showed 99.4% conversion to 2-amino-N-benzylacetamide mono-HCl.

[0267] The product slurry was filtered and the solid intermediate product (2-amino-N-benzylacetamide mono-HCl) was collected. The filter cake was washed twice with isopropanol; washing 1 (0.633 kg, 1 volume), washing 2 (0.328 kg, 0.5 volume), and the third time with methyl tert-butyl ether (MTBE); washing 3 times (0.641 kg, 1 volume) and dried under reduced pressure at 20°±5°C for 18 hours to obtain 0.760 kg of dried mono-HCl intermediate product. HPLC analysis showed that the purity of the mono-HCl product was 100.0%. The structure was confirmed by 1HNMR, and the dried intermediate product retained 0.23 wt% of volatiles from the drying loss test.

[0268] Cyclization of 2-amino-N-benzylacetamide monoHCl with 1-methylpiperidin-4-one

[0269] 2-amino-N-benzyl acetamide monoHCl (0.5 kg, 1 equivalent) and anhydrous ethanol (3.26 kg, 8.0 volumes, EtOH) are added to a nitrogen-purged reactor and stirred vigorously. 1-methylpiperidin-4-one (0.310 kg, 1.1 equivalents) is added to the reactor and rinsed with anhydrous ethanol (0.795 kg, 2 volumes). The reactor temperature is raised and maintained at 65 ° ± 5 ° C, and the reaction is carried out for 18 hours. HPLC analysis shows that 91% is converted into the cyclized product 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decane-2-one. The intermediate product slurry is cooled to 20 ° C ± 5 ° C, then filtered into a holding container, and then anhydrous ethanol rinse (0.207 kg, 0.50 volume) is added to provide a sol.

[0270] Conversion of the cyclization product to 2HCl·H2O polymorph Form 1

[0271] 1-Benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one sol and anhydrous ethanol washing solution (0.201 kg, 0.50 volume) were added to the reactor and stirred. The temperature was raised and maintained at 50±5°C, while 30% (0.457 kg, 1.5 equivalents) of hydrochloric acid aqueous solution was slowly added to the reactor over 31 minutes, followed by washing with anhydrous ethanol (0.206 kg, 0.5 volume).

[0272] The reaction mixture was slowly cooled to 20°C ± 5°C within two hours and stirred for another 4 hours while being maintained at this temperature. The temperature was further cooled to -15 ± 5°C within 2 hours, and the reaction mixture was stirred for another 11 hours while being maintained at this temperature. The slurry product 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decane-2-one diHCl H2O obtained by filtration separation. The filtered solid was washed three times with anhydrous ethanol at 15 ± 5°C (about 2 volumes each time), then slurried twice in EtOAc (about 2 volumes each time) and filtered. The final product was collected after drying at 20 ± 5°C for 23 hours.

[0273] HPLC analysis showed that the final product was 100.0% pure. The structure was confirmed by 1HNMR, 13C-NMR and 2D-NMR. The water content of the monohydrate product was 5.5% by weight, determined by Karl Fischer titration. Figure 1 In comparison, polymorph Form 1 of the crystalline monohydrate product was confirmed by X-ray powder diffraction (XRPD).

[0274] Dihydrochloride polymorph Form 2 monohydrate

[0275] About 9.6 g of compound C0105 free base was mixed with 30 mL of 2-propanol. The resulting suspension was stirred at 50°C for about 1 hour, and then an aqueous solution of 37% HCl (9.3 mL, 3 equivalents) in 10 mL of 2-propanol was added dropwise. A white suspension was obtained, which was stirred at 50°C for about 1 hour, then at ambient room temperature for 1 hour, and finally at about 2°C for 1 hour. The solid material was recovered by vacuum filtration and suspended in a mixture of acetone / water (20% water, 8 mL). The resulting slurry was temperature cycled between ambient and 40°C in a 4-hour cycle. The resulting solid was filtered and XRPD analysis after drying showed a new polymorphic form, labeled Form 2 dihydrochloride hydrate, and its XRPD spectrum is shown in Figure 2 middle.

[0276] Dihydrochloride Polymorph Form 3 DMA Solvate

[0277] Approximately 25 mg of HCl di-salt (conversion of scaled-up batches from HCl mono-salt to di-salt) was placed in a vial and a 0.1 mL aliquot of dimethylacetamide was added. Between each addition, the mixture was checked for dissolution, and if no dissolution was evident, the mixture was heated to about 50°C and checked again. This procedure was continued until 2 mL of solvent was added (no dissolution occurred).

[0278] The slurry was then temperature cycled between ambient temperature (about 22°C) and 40°C in 4 hour cycles for about 3 or 4 days (cooling / heating rate after 4 hour cycle was about 1°C / minute). The slurry was cooled, filtered, and the recovered solid was dried under ambient conditions before analysis. The XRPD spectrum is shown in Figure 3 middle.

[0279] Dihydrochloride Polymorph Form 4 - Amorphous

[0280] About 25 mg of the di-HCl salt was slurried in 300-1000 μL of heptane or toluene. The mixture was then temperature cycled (between 40°C and RT). The resulting solid was filtered and dried under vacuum. Analysis of the solid showed a unique XRPD pattern labeled Form 4, which did not contain peaks such as Figure 4 shown.

[0281] Dihydrochloride Polymorph Form 5 Monohydrate

[0282] About 20 mL of methanol was added to about 450 mg of di-HCl salt hydrate (Form 1). The resulting suspension was stirred at 50 °C for about 3 hours, and the resulting solution was filtered at ambient temperature. The separated gel / solid mixture was vacuum dried and mixed with about 0.1 mL of methanol. The resulting slurry was temperature cycled between ambient temperature and 40 °C in 4 hour cycles. The resulting solid was then filtered and vacuum dried. Figure 5 XRPD spectral analysis of the spectrum showed a new polymorphic form which was labeled Form 5 monohydrate.

[0283] Mono-HCl salt, Form 1

[0284] About 3.5 g of compound C0105 free base was dissolved in about 1 mL of 2-propanol at 40°C, and 1 equivalent of 37% HCl (1.128 mL) in 1.9 mL of 2-propanol was added dropwise to the mixture under stirring at 40°C, and the resulting mixture was cooled from 40°C to 5°C at a rate of about 1°C / min. A suspension was obtained and stirred at ambient room temperature for another 3 hours. The resulting white solid was filtered and dried under ambient conditions before analysis. About 2.5 g of material was recovered as this new polymorphic form labeled Form 1. An additional 0.2 g of solid was obtained from the mother liquor of this preparation by stirring at 5°C for about 24 hours, resulting in a total yield of 34%. The XRPD spectrum of this solid polymorph compound is shown in Figure 6 middle.

[0285] Mono-HCl salt, Form 2

[0286] About 500 mg of C0105M free base was dissolved in 6 mL of 2-propanol and mixed with 1 equivalent of HCl (37%) dissolved in 2 mL of 2-propanol. The resulting solution was temperature cycled (between 40°C and RT, 4 hour cycles) for 3 days. The XRPD spectrum of the solid polymorph is shown in Figure 7 middle.

[0287] Mono-HCl salt, Form 3

[0288] Prepared as Form 2 above, but the solid was dried under vacuum. The XRPD spectrum of this solid polymorph is shown at Figure 8 middle.

[0289] Mono-HCl salt, Form 4

[0290] The mother liquor and the solid material recovered from the preparation of Form 2 above were mixed together and seeded with about 10 mg of HCl salt, which was obtained by dissolving about 500 mg of C0105M free base in 6 mL of 2-propanol and mixed with 1 equivalent of HCl (37%) dissolved in 2 mL of 2-propanol. The resulting solution was temperature cycled (4 hour cycles between 40°C and RT) for 3 days. The solid obtained from the temperature cycle was dried under vacuum. The slurry obtained thereafter was then temperature cycled between 40°C and 20°C for 24 hours and analyzed by DVS between 0-90% RH (in 10% increments) and 90-0% RH. The XRPD spectrum of the solid polymorph is shown in Fig. 9 middle.

[0291] Free base form 1

[0292] The free base material used to prepare free base Forms 1, 2 and 3 was obtained as a yellow gummy solid which appeared to be amorphous. This material was prepared as described above under the heading "Preparation 2" and stopped before the final addition of hydrochloric acid in the final step as shown.

[0293] Approximately 500 mg of the free base material was slurried in 0.5 mL of ethyl acetate and the resulting mixture was temperature cycled (4 hour cycles between 40°C and RT) for 3 days. Upon cooling, a crystalline polymorph precipitated and was recovered and referred to herein as free base Form 1. The XRPD spectrum of this solid polymorph is shown in Fig.10 .

[0294] Free base form 2

[0295] 2.4 grams of C0105M free alkali peptoids are dissolved in 8.4 mL methanol, and 100 μ L aliquots are transferred to 96 vials respectively. Evaporation of solvent under ambient conditions leaves about 25 mg C0105M in each of 96 vials. Add 300 microlitres of ethyl acetate to obtain jelly. Between ambient temperature (about 22 ° C) and 40 ° C, temperature cycles are carried out for about 3 or 4 days (cooling / heating rate after the 4 hour cycle is about 1 ° C / minute) to provide free alkali form 2 crystals. The XRPD spectrum of this solid polymorph is shown in Fig.11 middle.

[0296] Free base form 3

[0297] Physical manipulation of the surface of the resulting free base gum with a spatula provided a white viscous powder. HPLC analysis of the powder indicated a purity of 96.5% of the free base compound. Polarized light microscopy (PLM) analysis indicated that the material was birefringent under polarized light and had a blocky morphology. XRPD analysis indicated that the material thus obtained was crystalline. The XRPD spectrum of the polymorph is shown in Fig.12middle.

[0298] result

[0299] program

[0300] X-ray powder diffraction (XRPD)

[0301] XRPD analysis was performed on a Siemens D5000, scanning the samples between 3 and 30° (or 50° for input materials) 2θ (2θ). For samples <100 mg, 10-20 mg of material was gently pressed onto a glass disk inserted into the XRPD sample holder. For samples <20 mg, 5-10 mg of material was gently pressed onto a zero background disk inserted into the XRPD sample holder. For samples >100 mg, approximately 100 mg of material was gently pressed into a plastic XRPD sample holder to ensure a smooth sample surface just above the level of the sample holder. The samples were then loaded into a Siemens D5000 or Panalytical X'Pert diffractometer operating in reflection mode and analyzed using the following conditions:

[0302]

[0303] Further XRPD analysis was performed on a Panalytical X'pert (PANalytical BV, Westborough, MA) powder, scanning the sample between 3 and 35° 2θ. The material was lightly ground and loaded onto a porous plate with Kapton® polyimide or Mylar® polyester film to support the sample. The porous plate was then loaded into a PANalytical diffractometer (Westborough, MA) operating in transmission mode and analyzed using the following experimental conditions.

[0304]

[0305] Other XRPD analyses were performed on a Bruker D2 phase analyzer with a zero background pan inserted in the XRPD sample holder. The following method was used:

[0306]

[0307] Polarized Light Microscopy (PLM)

[0308] The presence of crystallinity (birefringence) was determined using an Olympus® BX50 polarizing microscope equipped with a Motic® camera and image capture software (Motic® Images Plus 2.0). Unless otherwise stated, all images were recorded using a 20X objective.

[0309] Thermogravimetric analysis (TGA)

[0310] Approximately 5 mg of material was weighed into an open aluminum pan and loaded into a simultaneous thermogravimetric / differential thermal analyzer (TG / DTA) and kept at room temperature. The sample was then heated from 25°C to 300°C at a rate of 10°C / min, during which the change in sample weight and any differential thermal events (DTA) were recorded. Nitrogen was used as a purge gas with a flow rate of 100 cm 3 / minute.

[0311] Differential Scanning Calorimetry (DSC)

[0312] About 5 mg of material was weighed into an aluminum DSC pan and sealed non-hermetically with a perforated aluminum lid. The sample pan was then loaded into a Seiko DSC6200 (equipped with a chiller) cooled and maintained at 25°C. Once a stable heat flow response was obtained, the sample and reference sample were heated to about 240°C at a scan rate of 10°C / min and the resulting heat flow response was monitored.

[0313] 1 H Nuclear Magnetic Resonance (NMR)

[0314] In the Bruker AV400 ( 1 H frequency: 400 MHz) 1 H NMR studies. Each sample was carried out in DMSO-d6 or CDCl3 1 H NMR studies were performed and samples were prepared to a concentration of approximately 10 mg / mL.

[0315] Infrared spectroscopy (IR)

[0316] Infrared spectroscopy was performed on a Bruker ALPHA P spectrometer. Sufficient material was placed on the center of the plate of the spectrometer and the spectrum was acquired using the following parameters:

[0317]

[0318] Dynamic Vapor Sorption (DVS)

[0319] About 10 mg of sample was placed in a glass vapor sorption balance pan and loaded into a DVS-1 dynamic vapor sorption balance by a surface measurement system. The sample was subjected to a gradual change curve from 0% -90% relative humidity (RH) in 10% increments, holding the sample at each step until a stable weight was achieved (99.5% step completion). After the adsorption cycle was completed, the sample was dried from 90% RH to 0% RH using the same procedure. The weight change during the adsorption / desorption cycle was plotted, allowing the hygroscopicity of the sample to be determined.

[0320] Karl Fischer Colorimetric Titration (KF)

[0321] About 10-15 mg of solid material is accurately weighed into a vial. The solid is then manually introduced into the titration cell of a Mettler Toledo C30 mini titrator. The vial is weighed back after the solid is added, and the weight of the added solid is entered into the instrument. Once the sample is completely dissolved in the cell, the titration begins. The water content is automatically calculated by the instrument in percentage and the data is printed.

[0322] High performance liquid chromatography (HPLC)

[0323]

[0324] Ion chromatography (IC)

[0325]

[0326] pKa analysis

[0327] The potentiometric parameters for pKa studies were developed by Absorption Systems® and were performed as follows: Three titrations were performed in water with the ionic strength adjusted to 0.15 with KCl (ISA water) over a pH range of 3.0-11.5.

[0328] program:

[0329] Compound titrations were performed in ISA water at 22°C. A weighed amount of TC (2.40 mg) was placed in a titration vial. ISA water (15 mL) was automatically delivered to the vial. The pH of the solution was adjusted to 3 by the automatic addition of 0.5M HCl. Titration was performed automatically with 0.5M KOH until the pH reached 11.5. Another volume of ISA water was added to the titration bottle to perform a second and third titration in each titration, respectively. The data sets of the three titrations were merged in the Refinement Pro program to generate a multiset for pKa calculations.

[0330] First, the pKa measurement and calculation of compound C0105 was performed assuming two basic ionizable groups. The lower value was found to be pH 1.5. The pKa calculation of the compound was then performed assuming one basic ionizable group. The pKa values ​​were found to be 8.0 and 1.5, as shown below for the pKa values ​​of each amine nitrogen.

[0331]

[0332] Evaluation of the prepared HCl monosalt

[0333] A. Stability Test

[0334] Each salt formed was exposed to 40°C / 75% RH (open vial), elevated temperature (80°C, open vial) and ambient light (about 22°C in closed vial) for 1 week to evaluate both chemical and physical stability. The resulting solids were analyzed by X-ray powder diffraction (XRPD) to determine if any changes occurred, and the purity was determined by HPLC.

[0335] B. Salt disproportionation studies

[0336] Each salt was slurried in water at room temperature (about 22°C) and excess solids were removed at 1, 24 and 48 hours and analyzed by XRPD. The pH of the supernatant was also monitored.

[0337] C. Hydration Studies

[0338] Slurries of each salt were created in IPA:water mixtures (95%:5%, 90%:10%, and 60%:40% water) and stirred at ambient temperature (about 22° C.) for about 48 hours. The resulting solids were then analyzed by XRPD to determine if any crystalline form changes occurred upon slurrying.

[0339] D. Thermodynamic Solubility Studies

[0340] Attempts were made to generate slurries of each salt (approximately 20 mg) in different aqueous buffer media (PBS, FaSSIF, FeSSIF, and SGF; Biorelevant.com) at ambient temperature (approximately 22° C.) for approximately 48 hours. The resulting samples were found to be too soluble in the buffer media (>200 mg / mL) to be studied. See the following buffer compositions:

[0341] PBS

[0342] 0.014 g KH2PO4, 0.9 g NaCl, and 0.079 g Na2HPO4 anhydrous in 100 mL deionized water.

[0343] Fasting state simulated intestinal fluid (FASSIF)

[0344] 0.021 g NaOH, 0.198 g NaH2PO4 (monohydrate), 0.309 g NaCl and 0.112 g SIF powder (Biorelevant.com Ltd, London, UK) were dissolved in 0.050 mL deionized water.

[0345] Fed State Simulated Intestinal Fluid (FeSSIF)

[0346] 0.202 g NaOH, 0.433 g glacial acetic acid, 0.594 g NaCl and 0.560 g SIF powder (Biorelevant.com Ltd, London, UK) were dissolved in 0.050 mL deionized water.

[0347] Simulated gastric fluid (SFG)

[0348] 0.200 g NaCl and 0.006 g SIF powder (Biorelevant.com Ltd, London, UK) in 100 mL deionized water.

[0349] Primary polymorph screening of HCl disalt hydrate

[0350] A. Temperature Cycle

[0351] In order to make effective use of materials, the samples recovered from the solvent solubility screening are also used for primary polymorph screening. If a suspension is obtained during the solvent solubility screening, the mixture is directly used for polymorph screening, and if a solution is obtained, more solid material is added to obtain a slurry. The suspension is then subjected to temperature cycling for about 3 or 4 days (the cooling / heating rate after 4 hours is about 1°C / minute) between ambient temperature (about 22°C) and 40°C in a 4-hour cycle. The mixture is filtered, and the recovered solid is dried under ambient conditions before analysis, while the mother liquor is retained for further study.

[0352] B. 2℃~-18℃ quenching

[0353] A quench study was conducted by placing a saturated solution of the HCl di-salt in each of the 24 selected solvent systems at about 2°C, and if no solid material was recovered after 72 hours, the non-aqueous solution was placed in a -18°C environment for at least 72 hours. Any solid material was then recovered and analyzed by XRPD and PLM.

[0354] C. Slow evaporation

[0355] Slow evaporation studies were performed by evaporating a saturated HCl di-salt solution at ambient temperature (about 22°C) and pressure. Any solid material was then recovered and analyzed by XRPD and PLM.

[0356] D. Add antisolvent at ambient temperature and 2°C

[0357] Antisolvent addition studies were performed at ambient temperature (about 22°C) by adding the selected antisolvent (acetone or ethanol) to a saturated solution of the HCl di-salt in each of the 24 selected solvent systems. Antisolvent addition was continued until no more precipitation occurred or until no antisolvent could be added. Antisolvent addition studies were also performed at low temperature (2°C) on saturated solutions recovered from quench experiments that did not produce any solids. Any solid material was recovered and rapidly analyzed by PLM and XRPD to prevent form changes.

[0358] E. Proportional increase of HCl disalt hydrate form 2

[0359] About 0.6 mL of acetone / water (20% water) mixture was added to about 450 mg of HCl di-salt (Form 1). The resulting slurry was temperature cycled between ambient temperature (about 22° C.) and 40° C. in 4 hour cycles for about 4 days. The solid was filtered and XRPD analysis was performed before and after drying.

[0360] F. Proportional increase of HCl disalt hydrate form 5

[0361] About 20 mL of methanol is added to about 450 mg of HCl di-salt (Form 1). The resulting suspension is stirred at 50 ° C for about 3 hours, the resulting solution is filtered, and it is evaporated at ambient temperature (about 22 ° C). The gel / solid mixture obtained by evaporation is vacuum dried and mixed with about 0.1 mL of methanol. The resulting slurry is temperature cycled between ambient temperature (about 22 ° C) and 40 ° C for about one day in a 4-hour cycle. The recovered solid is filtered and analyzed by XRPD analysis before and after drying.

[0362] Full physical characterization of HCl monosalt (Form 1)

[0363] HPLC analysis showed a purity of 98.8%.

[0364] When compared to the free base, 1 H-NMR analysis observed peak shifts, indicating salt formation. Traces of IPA were also observed in the spectrum.

[0365] A 1:1 ratio between the API and the chloride counter ion was observed by IC analysis, indicating the formation of a monosalt.

[0366] TG / DT analysis showed a small weight loss of 0.2% below 180°C, followed by another small weight loss of about 0.5%, corresponding to the endotherm observed at the beginning of the DT trace at 184°C, and degradation starting above 190°C.

[0367] KF analysis showed a water content of about 0.15%.

[0368] DSC analysis showed a large endotherm initially at 180 °C, which most likely corresponds to melting.

[0369] DVS analysis showed that the material was very hygroscopic above 70% RH. Adsorption cycles showed no significant increase in mass until 60% RH (water uptake of about 0.27%). A steady mass increase was observed between 60% and 70% RH (water uptake of 2.55% at 70% RH), and a sharp mass increase was observed between 70% and 90% RH (water uptake of 68.57% at 90% RH). Desorption cycles showed a steady decrease in mass of 54.25% between 90% and 50%, and a further decrease of 6.10% between 10% and 0%. A hysteresis of 7.3% was observed at 0% RH. The material deliquesces at high RH.

[0370] Post-DVS XRPD analysis showed that the material was inconsistent with any form previously observed for the HCl monosalt. This finding supports the observation that the material deliquesced during the analysis and then recrystallized into a new form upon drying.

[0371] Stability study (1 week)

[0372] The results and observations from the stability studies of the HCl salt are reported in the table below.

[0373] During stability studies by HPLC analysis, no significant loss of purity was observed.

[0374] XRPD analysis showed that the material maintained its polymorphic form during the 1-week stability study at ambient temperature and 80°C. At 40°C / 75% RH, the material deliquesced during the 1-week period, which was consistent with the DVS analysis. A small loss of crystallinity was also observed during the stability study.

[0375] 1-week results and observations

[0376] Study on the Stability of HCl Monosalt

[0377]

[0378] Solvent Solubility Screening of HCl Monosalt

[0379] The results of the solvent solubility screen of the HCl monosalt are reported in the table below. The screen indicated that the HCl monosalt had poor solubility in most of the selected solvent systems. However, very high solubility was observed in methanol, 2-propanol:water (10%), acetone:water (20%), and water, and high solubility was observed in dimethyl sulfoxide. Some solubility was also observed for dimethylacetamide, ethanol, and acetone:water (5%).

[0380] Single HCl-Solubility Screening Results

[0381]

[0382] Physical Characterization of HCl Disalt Hydrate, Form 1

[0383] The XRPD diffractogram indicated that the material was consistent with the obtained disalt.

[0384] PLM analysis revealed that between crossed polarities the material was birefringent with a bulky morphology.

[0385] HPLC analysis showed a purity of 99.1%.

[0386] 1 H-NMR analysis showed a peak shift at upfield compared to the input material indicating salt formation. A small amount of solvent (2-propanol) was also observed in the spectrum. Furthermore, the spectrum was consistent with the analysis of the received HCl di-salt.

[0387] TG / DT analysis showed three consecutive weight losses below 200°C, namely:

[0388] 1) 5.4%, which corresponds to the endotherm in the DT trace starting at 81 °C (about 5.2% is expected to be the monohydrate);

[0389] 2) 1.7%, which corresponds to the endotherm in the DT trace starting at 146°C; and

[0390] 3) 0.6%, which corresponds to the exotherm in the DT trace with a peak of 170°C.

[0391] Decomposition was observed at >200°C.

[0392] A moisture content of about 5.5% was observed by KF analysis, which seems to be consistent with the TG analysis.

[0393] By DVS analysis, the material appears to be hygroscopic above 50% RH.

[0394] The adsorption cycles showed a small mass increase of about 0.56% between 0% and 50% RH, a steady mass increase between 50% and 80% (about 3.53% water uptake at 80% RH), and a sharp mass increase between 80% and 90% (about 8.26% water uptake at 90% RH).

[0395] The desorption cycle appears to follow the same trend as the adsorption between 90% and 70% RH, and then a steady mass decrease of approximately 2.33% is observed between 70% and 0%.

[0396] Small hysteresis was observed over the entire humidity range. Maximum hysteresis was observed at 50% RH, where the difference in water uptake between the adsorption and desorption curves was 0.78%. The final dry mass (at 0% RH, after adsorption and desorption curves) was observed to be 0.13% higher than the initial dry mass.

[0397] By XRPD analysis, no significant differences in polymorphic forms were observed after DVS.

[0398] HCl disalt hydrate, Form 1

[0399] Stability study (1 week)

[0400] The results and observations from the stability studies of the HCl di-salt are reported in the table below.

[0401] HPLC analysis showed the following purities: 99.4% (ambient), 99.0% (40°C / 75% RH), and 99.4% (80°C), respectively.

[0402] No significant changes in polymorphic form were observed in the stability studies of the HCl di-salt, Form 1 by XRPD analysis.

[0403] 1-week results and observations

[0404] Stability Study of HCl Disalt Hydrate Form 1

[0405]

[0406] Solvent Solubility Screening of HCl Disalt Hydrate, Form 1

[0407] The results of the solvent solubility screen for the HCl di-salt are reported in the table below. The screen indicated that the HCl di-salt was poorly soluble in most of the selected solvent systems, however very high solubility was observed in dimethyl sulfoxide and water. High solubility was also observed in acetone:water (20%). Moderate solubility was observed in 2-propanol:water (10%) and methanol.

[0408] Solubility Screening Results of HCl Disalt Hydrate - Form 1

[0409]

[0410] Primary polymorph screening of HCl disalt hydrate, Form 1,

[0411] The results of the primary polymorph screen of the HCl di-salt are summarized as follows, wherein Form 1 crystals were temperature cycled in the above solvents, the solvent was evaporated when the HCl di-salt was present, the solvent-HCl di-salt combination was quenched to 2°C or quenched to -18°C, the anti-solvent was added at ambient temperature and added at 2°C.

[0412] Five crystalline forms were identified as well as an amorphous form obtained by quenching to 2°C from all solvents except those containing added water and dimethylacetamide.

[0413] A total of five polymorphic forms were observed:

[0414] Form 1 (hydrate) ‒ input material and observed from a number of studies;

[0415] Form 2 (hydrate);

[0416] Form 2 (pure phase) – temperature cycling in acetone:water (20%);

[0417] Form 2 (mixture) – temperature cycling in acetonitrile, acetone:water (10%) and 2-propanol:water (10%);

[0418] Form 3 (solvate) – temperature cycling in DMA;

[0419] Form 4‒slow evaporation in heptane and toluene;

[0420] Form 5 (hydrate);

[0421] Formation 5 (pure phase)‒evaporation in methanol;

[0422] Formation 5 (mixture) ‒ evaporated in DMSO, 2-propanol and acetone:water (5%), quenched in water, antisolvent added in water.

[0423] Forms 1, 2, and 5 appeared to have the highest levels of crystallinity and were selected for the second polymorph screen.

[0424] Stability studies of polymorphs of Form 1, Form 2 and Form 5

[0425] Two kinds of each about 20 mg of form 1, form 2 and form 5 di-HCl salt are mixed together, and suspended with selected solvent system to obtain slurry.Then the gained suspension is stirred for about 3 days at different temperatures respectively.The table below lists the list comprising research details.The solid recovered by filtration is analyzed to illustrate the main polymorph form recovered by XRPD analysis.

[0426] Table Polymorph Stability Study

[0427]

[0428] Stability studies of polymorphs of Form 1, Form 2 and Form 5

[0429]

[0430] Some studies were conducted using water as the solvent, in which the compound is fairly soluble. If a clear solution was obtained, Form 1 was formed by evaporation of the solvent or slow cooling. If not enough water was added so that the slurry could not be stirred, no conversion to another polymorph was observed.

[0431] When a certain amount of water is added to obtain a good stirrable suspension, Form 2 is found. Cooling or evaporating the suspension gives good crystalline Form 2. To obtain this suspension, only 0.8 volumes of water need to be added, 0.7 volumes give a thick paste, and 1.0 volumes give a clear solution. Other water miscible solvents such as isopropyl alcohol (IPA) can be mixed with water to broaden the useful range of solvents to solids to provide Form 2 polymorph.

[0432] Scaled-up form 2 (10g)

[0433] Form 2 was successfully scaled up to reproduce at 99.4% purity by HPLC on a 10 g scale. However, some loss of crystallinity was observed upon drying. Improvements in crystallinity were observed during hydration studies that did not change the polymorph form after DVS analysis and during stability studies at 40°C and 75% RH, likely due to water absorption in the crystal lattice.

[0434] Between 0% and 50% RH, this material exhibited lower hygroscopicity than Form 1, but was greater than Form 1 by >50% RH DVS analysis: approximately 0.2% water uptake was observed at 50% RH and 24.9% at 90% RH by DVS analysis (approximately 0.6% for Form 1 at 50% RH and 8.3% at 80% RH).

[0435] Form 2 was also found to be more sensitive to higher temperatures than Form 1; after a 1-week stability study at 80°C, a color change (white to off-white / orange) and a purity of approximately 95.5% were observed by HPLC analysis.

[0436] XRPD analysis indicated that Form 2 obtained from the scale-up appeared consistent with the results seen initially. However, a loss of crystallinity was observed upon drying, which may be due to partial removal of water from the lattice.

[0437] PLM analysis showed a plate-like / lathe-like morphology.

[0438] TG / DT analysis showed two consecutive weight losses: 0.7%, corresponding to the endotherm in the DT trace starting at 70.5°C, and 4.8% (about 5.2% expected for the monohydrate), corresponding to the endotherm in the DT trace at 128°C.

[0439] KF analysis showed a water content of about 6.1%.

[0440] DSC analysis showed an initial small endotherm at 76.9°C, probably due to unbound solvent (IPA and / or acetone), followed by a large, broad endotherm at 144.9°C, probably due to water loss, followed by an exotherm at 164.6°C.

[0441] By DVS analysis, the material appears to be hygroscopic above 50% RH.

[0442] The adsorption cycles showed no significant mass increase between 0% and 50% RH (water uptake was about 0.2% at 50% RH), a steady mass increase was observed between 50% and 80% RH (water uptake was about 9.9% at 80% RH), and a sharp mass increase between 80% and 90% RH (water uptake was about 24.9% at 90% RH).

[0443] Between 90% and 70%, the desorption cycle appears to follow the same trend as the adsorption cycle, and then a gradual decrease in mass of 6.77% is observed between 70% and 0%.

[0444] At 0% RH, a small hysteresis (ie, water retention) of approximately 0.4% RH was observed upon desorption.

[0445] Post-DVS XRPD analysis showed an increase in crystallinity compared to the dry input material, which may be due to the reintroduction of water into the lattice and subsequent crystallization of some amorphous components.

[0446] Purity of 99.4% was observed by HPLC analysis.

[0447] IC analysis showed an API:HCl ratio of approximately 1:2, as expected for the HCl di-salt.

[0448] Form 2 1 The H-NMR spectrum showed some additional peaks compared to Form 1, in particular a multiplet at δ: 8.91, a broad singlet at δ: 8.14, and three doublets at δ: 4.35, 3.61, and 2.84.

[0449] FT-IR analysis was obtained as a reference.

[0450] Stability study (1 week)

[0451] HPLC analysis showed the following purities: 99.5% (ambient), 99.8% (40°C / 75% RH), and 95.5% (80°C). A color change (white to off-white / orange) was also observed for samples stored at 80°C, which is consistent with a lower purity (95.5%). Both the color change and purity loss observations suggest that Form 2 is more sensitive to elevated temperatures than Form 1, although Form 2 appears to be more stable at ambient temperature.

[0452] XRPD analysis did not show significant changes in polymorphic form at both ambient and 80°C during the stability study of HCl disalt hydrate Form 2. However, an increase in crystallinity was observed at 40°C / 75% RH (probably due to water absorption in the crystal lattice and subsequent crystallization of some amorphous components).

[0453] 1-week results and observations

[0454] Study on the Stability of HCl Disalt

[0455]

[0456] Hydration studies

[0457] The results and observations from the hydration studies of the HCl di-salt (Form 2) are reported in the table below.

[0458] XRPD analysis showed that no form change occurred after stirring for 24 h in various IPA / water mixtures, suggesting no higher hydrate formation. An improvement in crystallinity was observed compared to the dried input material, which could be due to water absorption in the crystal lattice.

[0459] Results and Observations of Hydration Studies of HCl Disalt Hydrate (Form 2)

[0460] Research water% Water activity (approx.) IPA / water total volume (mL) observe 1 40 0.9 20 White suspension 2 10 0.7 60 White suspension 3 5 0.5 100 White suspension

[0461] The articles "a" and "an" are used herein to refer to one or to more than one (ie, to at least one) of the grammatical object of the article. For example, "an element" means one element or more than one element.

[0462] The foregoing description and examples are intended to be illustrative rather than restrictive. Other variations within the spirit and scope of the invention are possible and will readily suggest themselves to those skilled in the art.

Claims

1. A solid form of a compound of formula III selected from (a) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 1, wherein the crystalline form is characterized by an X-ray powder diffraction pattern comprising three peaks selected from 8.0, 13.0, 13.8, 19.1 and 20.2 2θ ± 0.2° 2θ; or Having an X-ray powder diffraction pattern as shown in FIG1 ; (b) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 2, wherein the crystalline form is characterized by an X-ray powder diffraction pattern comprising three peaks selected from 9.9, 11.9, 13.2, 14.2, 15.8, 20.0 and 20.4 2θ ± 0.2° 2θ; or Having the X-ray powder diffraction pattern of Figure 2; (c) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride dimethylacetamide solvate, Form 3, wherein the crystalline form is characterized by An X-ray powder diffraction pattern having the X-ray powder diffraction pattern of Figure 3; (d) amorphous 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride, Form 4, wherein the crystalline form is characterized by An X-ray powder diffraction pattern having the X-ray powder diffraction pattern of Figure 4; and (e) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 5, wherein the crystalline form is characterized by An X-ray powder diffraction pattern having the X-ray powder diffraction pattern of FIG. 5 .

2. The solid state form of claim 1, wherein the crystalline form is crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 1, and characterized in that An XRPD pattern comprising peaks at each of 8.0, 13.0, 13.8, 19.1 and 20.2 2Θ (± 0.2° 2Θ).

3. The solid state form of claim 1 or claim 2, wherein the crystalline form is crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one dihydrochloride monohydrate, Form 1, and the XRPD pattern further comprises 9.2, 15.4, 16.1, 19.7, 21.7, Peaks at 22.8, 23.2 and 24.2 2θ (±0.2° 2θ).

4. The solid state form of claim 1 or claim 2, wherein the crystalline form is crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one dihydrochloride monohydrate, Form 1, and the XRPD pattern further comprises 9.2, 15.4, 16.1, 19.7, 21.7, At least 3 peaks at 22.8, 23.2 and 24.2 2θ (± 0.2° 2θ).

5. The solid state form of claim 1 or claim 2, wherein the crystalline form is crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one dihydrochloride monohydrate, Form 1, and the XRPD pattern further comprises 9.2, 15.4, 16.1, 19.7, 21.7, At least 5 peaks at 22.8, 23.2 and 24.2 2θ (± 0.2° 2θ).

6. The solid state form of claim 1 or claim 2, wherein the crystalline form is crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-dec-2-one dihydrochloride monohydrate, Form 1, and the XRPD pattern further comprises peaks at each of 9.2, 15.4, 16.1, 19.7, 21.7, 22.8, 23.2, and 24.2 2θ (±0.2° 2θ).

7. The solid state form of claim 1 or claim 2, wherein the crystalline form is crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one dihydrochloride monohydrate, Form 1, and wherein the crystalline form is characterized by the XRPD pattern of Figure 1.

8. The solid state form of claim 1 or claim 2, wherein the water content of the crystalline form is determined by Karl Fischer titration.

9. A crystalline form of a compound of formula II, selected from (a) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 1, wherein the crystalline form is characterized by An X-ray powder diffraction pattern comprising three peaks selected from 12.4, 20.5, 21.7 and 25.5 2θ ± 0.2° 2θ; or Having an X-ray powder diffraction pattern as shown in FIG6 ; (b) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 2, wherein the crystalline form is characterized by an X-ray powder diffraction pattern comprising peaks at 10.5, 13.8 and 22.7 2θ ± 0.2° 2θ; or Having the X-ray powder diffraction pattern of FIG7; (c) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 3, wherein the crystalline form is characterized by An X-ray powder diffraction pattern comprising three peaks selected from 13.6, 15.8, 20.8, 22.0 and 27.2 2θ±0.2° 2θ; or having an X-ray powder diffraction pattern of FIG8 ; and (d) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one monohydrochloride, Form 4, wherein the crystalline form is characterized by an X-ray powder diffraction pattern comprising peaks at 11.2, 18.0 and 20.0 2θ ± 0.2° 2θ; or The X-ray powder diffraction pattern is shown in FIG9 .

10. A crystalline form of a compound of formula I selected from (a) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one free base, Form 1, wherein the crystalline form is characterized by an X-ray powder diffraction pattern comprising peaks at 24.1, 26.3 and 27.3 2θ ± 0.2° 2θ; or Having the X-ray powder diffraction pattern of Figure 10; (b) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one free base, Form 2, wherein the crystalline form is characterized by An X-ray powder diffraction pattern having the X-ray powder diffraction pattern of Figure 11; and (c) crystalline 1-benzyl-8-methyl-1,4,8-triazaspiro-[4.5]-decan-2-one free base, Form 3, wherein the crystalline form is characterized by an X-ray powder diffraction pattern comprising peaks at 10.1, 14.1 and 19.3 2θ ± 0.2° 2θ; or The X-ray powder diffraction pattern is shown in FIG12 .

11. A pharmaceutical composition comprising the solid form according to any one of claims 1 to 8, said solid form being dispersed in the pharmaceutical composition and being in an amount effective for treating and / or measuring Alzheimer's disease in a living patient.

12. Use of a pharmaceutical composition according to claim 11 for the manufacture of a medicament for the treatment and / or determination of Alzheimer's disease in a living patient.

13. A pharmaceutical composition comprising the crystalline form according to claim 9, the crystalline form being dispersed in the pharmaceutical composition and being in an amount effective for treating and / or measuring Alzheimer's disease in a living patient.

14. Use of a pharmaceutical composition according to claim 13 for the manufacture of a medicament for the treatment and / or determination of Alzheimer's disease in a living patient.

15. A pharmaceutical composition comprising the crystalline form according to claim 10, said crystalline form being dispersed in the pharmaceutical composition and being in an amount effective for treating and / or measuring Alzheimer's disease in a living patient.

16. Use of a pharmaceutical composition according to claim 15 for the manufacture of a medicament for the treatment and / or determination of Alzheimer's disease in a living patient.

Citation Information

Patent Citations

  • Method of inhibiting tau phosphorylation

    US10017736B2

  • Alzheimer's disease assay in a living patient

    US10222368B2

  • Filamin A binding anti-inflammatory and analgesic

    US8653068B2

  • Alzheimer's disease assay in a living patient

    US9354223B2

  • Method for inhibiting growth of cancer cells

    US9433604B2